2022
DOI: 10.20473/jaki.v10i1.2022.111-121
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the National Health Insurance Uptake in Indonesia

Abstract: Background: Indonesia introduced a national health insurance program, the so-called Jaminan Kesehatan National (JKN), in 2014 to enhance health access for its citizens. However, unattained universal health coverage (UHC) such as participation target becomes a concern. Aims: This study aimed to examine the factors influencing JKN participation and propose a possible policy improvement to enhance UHC implementation Methods: A systematic review was performed based on PRISMA guidelines, and literature was collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Formal education level is often associated with literacy [ 20 , 32 ]. Health insurance literacy, the ability to understand what health insurance is, is a prominent factor in health insurance participation [ 18 ]. A proper understanding of health insurance will lead to a higher acceptance rate for participating in health insurance [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Formal education level is often associated with literacy [ 20 , 32 ]. Health insurance literacy, the ability to understand what health insurance is, is a prominent factor in health insurance participation [ 18 ]. A proper understanding of health insurance will lead to a higher acceptance rate for participating in health insurance [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lower education population could have difficulty understanding the abrupt and complex change in the NHI mechanism [ 11 , 16 , 32 ]. Higher education and adequate information are two things that are always related to higher health insurance literacy [ 16 , 18 , 32 ]. Thus, it is not surprising that, in several studies, people’s exposure to information sources, such as mass media, is also reported to increase the probability of people with no education background enrolling in a health insurance coverage [ 15 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Health Insurance does help a lot, but who will help JKN from a deficit if there are many cases of diseases that require huge costs. A systematic review conducted by Muhlis (2022) found that the low level of participation in the JKN program was due to various multidimensional factors. This factor is not only related to the ability to pay contributions, but many are due to individual and environmental internal factors.…”
mentioning
confidence: 99%